2021
DOI: 10.1093/eurjcn/zvab019
|View full text |Cite
|
Sign up to set email alerts
|

Good general health and lack of family history influence the underestimation of cardiovascular risk: a cross-sectional study

Abstract: Aims Underestimation of cardiovascular risk may interfere with prevention of cardiovascular diseases (CVDs). We investigate whether general health and family history of myocardial infarction (MI) are associated with underestimation of perceived cardiovascular risk, and if the participants’ calculated risk modifies that association. Methods and results The analysis sample consisted of 526 individuals, 50–64 years old, from a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…66 The majority of our study participants had inaccurate risk-perception of CVD risk, mainly due to CVD risk underestimation, which is also consistent with several studies that reported poor risk-perceptions agreement between patients' perceived and their FRS 10-year CVD risk calculated with tendencies for optimism (risk underestimation). 5,52,54,[61][62][63][64][65][66][67][68][69][70][71][72][73] The finding of consistently low agreements between patients' subjectively perceived and objectively predicted CVD risk in the present and several previous studies' findings may signal the importance of appraising patients' CVD risk factors. The paramount importance of studies of risk perceptions is their ability to uncover individuals' risk appraisal of a disease threat or a health condition and the ability to self-evaluate and construe its potential health consequences.…”
Section: Discussionmentioning
confidence: 79%
“…66 The majority of our study participants had inaccurate risk-perception of CVD risk, mainly due to CVD risk underestimation, which is also consistent with several studies that reported poor risk-perceptions agreement between patients' perceived and their FRS 10-year CVD risk calculated with tendencies for optimism (risk underestimation). 5,52,54,[61][62][63][64][65][66][67][68][69][70][71][72][73] The finding of consistently low agreements between patients' subjectively perceived and objectively predicted CVD risk in the present and several previous studies' findings may signal the importance of appraising patients' CVD risk factors. The paramount importance of studies of risk perceptions is their ability to uncover individuals' risk appraisal of a disease threat or a health condition and the ability to self-evaluate and construe its potential health consequences.…”
Section: Discussionmentioning
confidence: 79%
“…However, the statistical models were designed for health literacy, and therefore the results should be interpreted with caution. Furthermore, most participants in this study perceived their cardiovascular risk as low [32], which may explain why fewer participants than expected searched for information. Among the participants that searched for information to better understand their test results, individuals with sufficient health literacy were almost three times as likely to use the online national health information portal Healthcare Guide 1177.…”
Section: Discussionmentioning
confidence: 84%
“…However, the statistical models were designed for health literacy, and therefore the results should be interpreted with caution. Furthermore, most participants in this study perceived their cardiovascular risk as low [ 32 ], which may explain why fewer participants than expected searched for information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson and colleagues (2018) indicate significant discrepancy in African American women when it comes to the association between CVD risk factors and risk estimation [14]. Others indicate there is a difference in perception of symptoms for myocardial infarction; [15] recognizing a heart attack; [16] and how family members perceive risk during an out-ofhospital cardiac arrest and general health [17][18]. Education about how to decrease cardiac risk factors is often the priority for staying heart healthy [1][2][3][19][20][21].…”
Section: Introductionmentioning
confidence: 99%